The level of time management application in Libyan airports - الصكالي أيمن سالم عبد الكريم; الزروق الرشيد عبد الله (Scientific Journal of University of Benghazi, 2023)
Study summary: The study aimed to identify the level of time management application in Libyan pilot institutions through the following dimensions (time planning, time management, time directing, and time control), as well as knowing the differences between the participants' responses about the level of time management application due to demographic variables, and be The study population consisted of all employees in the management of Benina International Airport - Benghazi, who numbered (92) employees. The study followed the case study approach, and a questionnaire was used to collect the data of the initial study and analyze it using the (SPSS) program. There are no differences in the answers of the respondents working at Benina International Airport - Benghazi due to the variable (gender, age, educational level, length of service). The study also provided a set of recommendations that it is hoped that its followers will be followed to strengthen the time management system in the institution under study.